Synthesis and dielectric properties of Bi₃.₃₆Mg₁.₉₂₋ₓAₓNb₂.₇₂O₁₃.₇₆ (A = Ca, Sr AND Ba) pyrochlore systems - Mat Dasin, Nurul Aidayu (2017)
Bismuth magnesium niobate (BMN) pyrochlores are one of the potential dielectrics owing to their excellent dielectric properties, e.g. high relative permittivity, ε‟ > 160, low dielectric loss, tan δ in the order of ~10-4 and compositional tunable temperature coefficient of capacitance, TCC. In this work, alkaline earth metals namely, Ca, Sr and Ba were successfully introduced into BMN pyrochlores through solid-state reaction. These substitutional solid solutions were prepared with the proposed chemical formula, (Bi3.36Mg0.64-xAx)(Mg1.28Nb2.72)O13.76, in which the formation mechanism requires a one-to-one replacement of Mg2+ by A2+ (A2+ = Ca, Sr and Ba) at the eight-coordinated A site. The solid solution limits of (Bi3.36Mg0.64-xAx)(Mg1.28Nb2.72)O13.76 are found to be 0 ≤ x ≤ 0.7, 0 ≤ x ≤ 0.5 and 0 ≤ x ≤ 0.2 in the Ca-, Sr- and Ba-series, respectively. Cadoped BMN pyrochlores have a relatively extensive solid solution limit due to the closely similar ionic radii between Ca2+ and Bi3+ with their values of 1.12 Å and 1.13 Å, respectively. These materials adopted a cubic symmetry, space group Fd3m (No. 277), Z = 4, with their refined lattice parameters, a = b = c, decrease linearly from 10.5968(16) Å to 10.5332(14) Å, 10.5671(17) Å and 10.5879(3) Å, respectively. On the other hand, all BMCN, BMSN and BMBN pyrochlores are found to be thermally stable as thermal event is absent within the studied temperature range ~30−1000 °C. Whilst, the irregular shaped grains of surface morphologies of these samples showing a broad distribution of mean grain size with increasing of dopant concentration. Six IRactive phonon modes are observed in these chemically doped pyrochlores, which are due to the vibration and bending of metal-oxygen bond in the range 1000 cm-1−200 cm- 1. All the doped BMN pyrochlores appeared to be highly insulating with their conductivities in the order of ~10-6−10-5 Scm-1 at ~600 °C. These materials exhibited moderate high ε‟, low tan δ in the order of 10-3−10-1 at ~30 °C and negative TCC values, ~319−933 ppm/°C in the temperature range ~30−300 °C. The recorded ε‟ values of Ca-, Sr- and Ba-series are in the range 69−171, 90−186 and 147−183, respectively at ~30 °C and 1 MHz. The Arrhenius conductivity plots of these doped BMN pyrochlores showed linear and reversible characteristics in a heat-cool cycle. The activation energies of BMCN, BMSN and BMBN pyrochlores are found in the range 1.17−1.47 eV, 1.20−1.49 eV and 1.18−1.30 eV, respectively. The high activation energies, Ea > 1.0 eV are required for the electrical conduction, which is probably of a hopping electronic type. In attempts to investigate the electrical properties of pyrochlores in electrolyte, further studies have been performed by using pyrochlore thin films coated on indium tin oxide (ITO) glasses using cyclic voltametry (CV), galvanostatic charge-discharge (CD) and electrochemical impedance spectroscopy (EIS), respectively. Higher specific capacitance is recorded for 1-layer sample compared to 3- and 5-layer sample coated on ITO glasses in 1.0 M KCl electrolyte. The specific capacitance of 1-layer sample is found to decrease with increasing dopant concentration in respective Ca- Sr- and Baseries. On the other hand, the cyclic voltammogram curves of all the samples showed rectangular in shape without any pseudocapacitance effect, which is a common capacitive behaviour of electrochemical supercapacitors.